Electrolyte, battery and electric equipment

By using hydantoin and phosphate additives in the electrolyte of lithium-ion batteries, a stable SEI film is formed, which solves the problem of battery life attenuation, and achieves a longer service life and better high-temperature cycling performance.

CN119786720AActive Publication Date: 2025-04-08XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510005691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The life attenuation of lithium-ion batteries during circulation is mainly due to the insufficiency of the SEI film on the surface of the negative electrode sheet, which causes side reactions of lithium ions to occur on the surface and consume active lithium.

Method used

An electrolyte containing hydantoin additives and phosphate additives is adopted. The hydantoin additive has a heteroatomic nitrogen and a ring structure, which is easy to form a stable SEI film on the surface of the negative electrode sheet. The phosphate additives improve the thermal stability of the electrolyte through synergistic action.

Benefits of technology

The formed SEI film has high chemical stability and thermal stability, which slows down the possibility of lithium ions on the surface of the negative electrode sheet, extends the cycle life of the battery, and maintains good cycle performance under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786720A_ABST
    Figure CN119786720A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte, a battery and electric equipment. The electrolyte comprises a first additive and a second additive, the first additive is a hydantoin additive, and the second additive is a phosphate ester additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art

[0002] With the continuous development of energy storage technology, lithium-ion batteries are required to have a lower life attenuation amplitude and a longer service life. During the cycle of lithium-ion batteries, the battery life attenuation is mainly due to the fact that the SEI film on the surface of the negative electrode is not strong enough, and lithium ions react with the surface of the negative electrode, causing lithium to be deposited on the surface of the negative electrode in the form of salt. Therefore, in the long-term cycle of lithium-ion batteries, how to build a stronger SEI film is an important means to improve battery cycle performance and extend battery cycle life. Summary of the invention

[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device, wherein the electrolyte has good thermal stability.

[0004] The present application provides an electrolyte, which includes a first additive and a second additive, wherein the first additive is a hydantoin additive, and the second additive is a phosphate additive.

[0005] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 0.1≤a / b≤5.

[0006] Furthermore, the structural formula of the first additive is: Among them, R1 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, R2 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, and R3 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, nitro, and vinyl.

[0007] Furthermore, the first additive is selected from and At least one of .

[0008] Furthermore, the mass fraction a of the first additive is in the range of 0.05%≤a≤3%.

[0009] Furthermore, the structural formula of the second additive is: Wherein, R4, R5 and R6 are all selected from siloxy groups.

[0010] Furthermore, the second additive is selected from and At least one of the following, wherein TMS is a trimethylsilyl group and i-Pr is an isopropyl group.

[0011] Furthermore, the mass fraction b of the second additive is in the range of 0.1%≤b≤1%.

[0012] The present application also provides a battery, which includes: a positive electrode plate, a separator, a negative electrode plate and an electrolyte provided by the present application; the electrolyte is used to infiltrate the positive electrode plate, the separator and the negative electrode plate.

[0013] The present application also provides an electrical device, which includes: a device body and a battery provided in the present application, and the battery supplies power to the device body.

[0014] In the present application, the electrolyte includes a first additive, the first additive is a hydantoin additive, the first additive has heteroatom nitrogen and a ring structure, so that the first additive has a narrow electrochemical window, so that the first additive is easy to obtain electrons. When the electrolyte is applied to the battery, the first additive is easy to obtain electrons on the surface of the negative electrode plate, and the first additive is superior to other components in the electrolyte such as solvents, second additives, etc. to undergo reduction reactions, thereby preferentially forming a SEI (Solid Electrolyte Interface) film on the surface of the negative electrode plate. The SEI film formed by the first additive has a lower solubility in the electrolyte and has higher elasticity and adhesion, so that the SEI film formed by the first additive is not easily dissolved in the electrolyte, and is not easy to break during the deintercalation of lithium ions, which can slow down the side reactions of lithium ions on the surface of the negative electrode plate during the battery charge and discharge cycle, and can avoid excessive consumption of active lithium ions in the electrolyte, so that the electrolyte has better cycle stability. In addition, the electrolyte further includes a second additive, which is a phosphate additive. The first additive and the second additive have a synergistic effect and can effectively improve the thermal stability of the electrolyte. Specifically, when the first additive and the second additive are used together, the first additive undergoes a reduction reaction to break -C(O)-NR- to generate an intermediate product, and the intermediate product further reacts with the second additive, thereby breaking the -PO- structure in the second additive, facilitating the further formation of a C(O)-NR- structure, a -PR(=O)-NR- structure, and a phosphate structure, etc., so that the SEI film formed by the first additive and the second additive at the interface of the negative electrode plate not only has organic structures such as -C(O)-NR- and -PR(=O)-NR-, but also has inorganic structures such as lithium phosphate. The SEI film with inorganic components has higher ionic conductivity and thermal stability. Even if the battery is cycled at high temperature, the SEI film formed by the first additive and the second additive is not easily damaged, which can reduce the side reactions of active lithium ions in the electrolyte at the interface of the negative electrode plate and reduce the consumption of lithium ions, so that the electrolyte has better thermal stability and the battery has better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1A partial cross-sectional structural schematic diagram of a battery according to an embodiment of the present application;

[0017] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;

[0018] Figure 3 This is a circuit block diagram of an electrical device according to an embodiment of the present application.

[0019] Description of reference numerals:

[0020] 100 - battery, 110 - positive electrode plate, 120 - diaphragm, 130 - negative electrode plate, 140 - electrolyte, 200 - electrical equipment, 210 - equipment body. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0023] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0024] With the continuous development of energy storage technology, lithium-ion batteries are required to have a lower life attenuation amplitude and a longer service life. During the cycle of lithium-ion batteries, the battery life attenuation is mainly due to the side reaction of lithium ions on the surface of the negative electrode, causing lithium to be deposited on the surface of the negative electrode in the form of salt. Specifically, on the one hand, during the charging process of lithium-ion batteries, ester solvents are easily reduced on the surface of the low-potential negative electrode, causing the ester solvents to react with lithium ions and consume active lithium; on the other hand, lithium-ion batteries generally use graphite as the active material of the negative electrode, and the lithium ion de-lithiation and lithium insertion behavior in the negative electrode will cause the distance between the graphite layers to increase and decrease continuously, causing the SEI film on the surface of the negative electrode to be continuously pulled, exposing new graphite interfaces to contact and react with the electrolyte, thereby causing the consumption of active lithium ions. In the long-term cycle of lithium-ion batteries, how to build a more solid SEI film is an important means to improve battery cycle performance and extend battery cycle life.

[0025] See also Figure 1 The present application provides a battery 100, which includes: a positive electrode plate 110, a separator 120, a negative electrode plate 130 and an electrolyte 140 provided in the present application; the electrolyte 140 is used to infiltrate the positive electrode plate 110, the separator 120 and the negative electrode plate 130.

[0026] It can be understood that the separator 120 is disposed on one side of the positive electrode plate 110 , and the negative electrode plate 130 is disposed on the side of the separator 120 away from the positive electrode plate 110 .

[0027] It can be understood that the positive electrode sheet 110 , the separator 120 , and the negative electrode sheet 130 are stacked, and the positive electrode sheet 110 , the separator 120 , and the negative electrode sheet 130 form an electrode assembly.

[0028] Optionally, in some embodiments, the battery 100 is a lithium-ion battery.

[0029] It can be understood that the electrolyte 140 is used to infiltrate the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 to achieve the transmission of active ions in the battery 100 between the positive electrode sheet 110 and the negative electrode sheet 130. When the battery 100 is a lithium-ion battery 100, the active ions are lithium ions.

[0030] In the present embodiment, the battery 100 includes the electrolyte 140 provided in the present application, and the electrolyte 140 includes a first additive and a second additive, the first additive is a hydantoin additive, and the second additive is a phosphate additive, and the first additive and the second additive have a synergistic effect, so that the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 130 has good chemical stability and thermal stability, which can slow down the side reactions between other components in the electrolyte 140 and the negative electrode plate 130 and consume lithium ions in the electrolyte 140, and can also reduce the lithium ions lost in repair due to SEI film rupture, which can reduce the life attenuation amplitude of the battery 100, so that the battery 100 has good cycle performance even in a high temperature environment, and the battery 100 has a long service life.

[0031] The present application provides an electrolyte 140 , wherein the electrolyte 140 includes a first additive and a second additive, wherein the first additive is a hydantoin additive, and the second additive is a phosphate additive.

[0032] It can be understood that the electrolyte 140 also includes a solvent, and the solvent is used to dissolve the first additive and the second additive.

[0033] In this embodiment, the electrolyte 140 includes a first additive, which is a hydantoin additive. The first additive has heteroatom nitrogen and a ring structure, so that the first additive has a narrow electrochemical window, so that the first additive is easy to obtain electrons. When the electrolyte 140 is applied to the battery 100, the first additive is easy to obtain electrons on the surface of the negative electrode plate 130. The first additive is superior to other components in the electrolyte 140, such as solvents, second additives, etc., to undergo a reduction reaction, thereby preferentially forming a SEI (Solid Electrolyte Interface) film on the surface of the negative electrode plate 130. The SEI film formed by the first additive has a low solubility in the electrolyte 140, and has high elasticity and adhesion, so that the SEI film formed by the first additive is not easily dissolved in the electrolyte 140, and is not easily broken during the deintercalation process of lithium ions, which can slow down the side reaction of lithium ions on the surface of the negative electrode plate 130 during the charge and discharge cycle of the battery 100, and can avoid excessive consumption of active lithium ions in the electrolyte 140, so that the electrolyte 140 has good cycle stability. In addition, the electrolyte 140 also includes a second additive, which is a phosphate additive. The first additive and the second additive have a synergistic effect, which can effectively improve the thermal stability of the electrolyte 140. Specifically, when the first additive and the second additive are used together, the first additive undergoes a reduction reaction to break -C(O)-NR- to generate an intermediate product, and the intermediate product further reacts with the second additive, thereby breaking the -PO- structure in the second additive, which is convenient for further forming a C(O)-NR- structure, a -PR(=O)-NR- structure and a phosphate structure, etc., so that the SEI film formed by the first additive and the second additive at the interface of the negative electrode plate 130 not only has organic structures such as -C(O)-NR- and -PR(=O)-NR-, but also has inorganic structures such as lithium phosphate. The SEI film with inorganic components has higher ionic conductivity and thermal stability. Even if the battery 100 is cycled at high temperature, the SEI film formed by the first additive and the second additive is not easily damaged, which can reduce the side reactions of active lithium ions in the electrolyte 140 at the interface of the negative electrode plate 130 and reduce the consumption of lithium ions, so that the electrolyte 140 has better thermal stability and the battery 100 has better cycle performance.

[0034] It can be understood that the first additive has a narrow electrochemical window, that is, the HOMO energy of the first additive is higher and the LUMO energy is lower, wherein HOMO is the highest occupied molecular orbital of the first additive, and LUMO is the lowest unoccupied molecular orbital of the first additive. If the HOMO energy is higher, the first additive is easy to lose electrons, and if the LUMO energy is lower, the first additive is easy to gain and accept electrons.

[0035] It can be understood that the SEI film formed by the first additive and the second additive includes an organic layer containing amide and phosphoramide, and also includes an inorganic layer containing lithium phosphate.

[0036] It can be understood that in the terminology of this application, "high temperature" is relative to "normal temperature", normal temperature generally refers to room temperature, such as between 10° C. and 30° C., and high temperature generally refers to more than 30° C. This is only an example of high temperature and normal temperature, and should not be understood as a limitation on high temperature and normal temperature.

[0037] It can be understood that the electrolyte 140 also includes an electrolyte, and the electrolyte is a lithium salt, and the lithium salt includes but is not limited to lithium hexafluorophosphate. The electrolyte is dissolved in a solvent and is used to provide lithium ions for the battery 100.

[0038] Optionally, the solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.

[0039] In some embodiments, the first additive has the structural formula: Among them, R1 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, R2 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, and R3 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, nitro, and vinyl.

[0040] It can be understood that in the structural formula of the first additive, R1, R2 and R3 can be selected from the same group of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano and nitro, and R1, R2 and R3 can also be selected from different groups of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano and nitro.

[0041] It can be understood that halogens include fluorine (F), chlorine (Cl), bromine (Br), iodine (I) and astatine (At). Fluorine, trifluoromethyl, cyano and nitro are electron-withdrawing groups that can further reduce the LUMO energy of the first additive.

[0042] It can be understood that, in the terms of the present application, "at least one" means one or more, and "plurality" means greater than or equal to two.

[0043] In this embodiment, the structural formula of the first additive is The first additive has a ring structure and has two nitrogen atoms, so that the first additive obtains electrons on the surface of the negative electrode plate 130 in priority to other components in the electrolyte 140, and forms a stable SEI film, so as to slow down the reduction of the solvent in the electrolyte 140 on the surface of the negative electrode plate 130 and consume excessive lithium ions. In addition, when the first additive and the second additive are used together, the intermediate product formed by the reduction reaction of the first additive can be combined with the second additive, so that a SEI film containing organic components and inorganic components is formed on the surface of the negative electrode plate 130, so as to improve the thermal stability of the SEI film, and make the electrolyte 140 have better thermal stability. Furthermore, R1 and R2 can be selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, and R3 can be selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, nitro, and vinyl, which is beneficial to improve the richness of the components of the SEI film formed by the first additive, thereby further improving the thermal stability of the SEI film, and reducing the lithium ions consumed to repair the SEI film, so that the electrolyte 140 has better thermal stability and the battery 100 has a higher capacity retention rate.

[0044] In particular, when at least one of R1, R2 and R3 is selected from electron-withdrawing groups such as fluorine, trifluoromethyl, cyano and nitro, the electron-withdrawing group will reduce the LUMO energy of the first additive, making it easier for the first additive to obtain electrons, thereby ensuring that the first additive is superior to other components in the electrolyte 140 in forming a SEI film on the surface of the negative electrode plate 130. In addition, the SEI film formed by the first additive containing fluorine or trifluoromethyl has more lithium fluoride, and the inorganic component lithium fluoride can further reduce the solubility of the SEI film in the electrolyte 140, thereby slowing down the dissolution of the SEI film by the electrolyte 140 during the charge and discharge cycle, improving the thermal stability of the SEI film, and making the electrolyte 140 have better thermal stability.

[0045] In particular, when at least one of R1, R2 and R3 is selected from phenyl, the organic polymer containing phenyl can enhance the flexibility of the SEI film, and can reduce the possibility of the SEI film rupturing during repeated lithium removal and lithium insertion, thereby enhancing the stability of the SEI film and avoiding the consumption of excessive lithium ions in the electrolyte 140 due to the repair of the SEI film. The electrolyte 140 has good stability and the battery 100 has good cycle performance.

[0046] In some embodiments, the first additive is selected from and At least one of .

[0047] In this embodiment, when the first additive is selected from and When at least one of the above is present, the first additive can preferentially form a stable SEI film on the surface of the negative electrode plate 130 to isolate the electrolyte 140 and the negative electrode plate 130, slowing down the reduction reaction of the solvent in the electrolyte 140 on the surface of the negative electrode plate 130 and consuming excessive lithium ions. In addition, the first additive and the second additive have a synergistic effect, and the intermediate product formed by the reduction reaction of the first additive can be combined with the second additive to form a SEI film containing organic and inorganic components on the surface of the negative electrode plate 130, so as to improve the thermal stability of the SEI film and make the electrolyte 140 have better thermal stability. In particular, and Containing electron-withdrawing groups makes the first additive have lower LUMO energy, and the first additive is easier to obtain electrons, thereby ensuring that the first additive is superior to other components in the electrolyte 140 in forming a SEI film on the surface of the negative electrode plate 130. In addition, the SEI film formed by the first additive containing fluorine or trifluoromethyl has more lithium fluoride, and the inorganic component lithium fluoride can further reduce the solubility of the SEI film in the electrolyte 140, thereby slowing down the dissolution of the SEI film by the electrolyte 140 during the charge and discharge cycle, improving the thermal stability of the SEI film, and making the electrolyte 140 have better thermal stability. Containing phenyl, the first additive can form a polymer containing phenyl and form a SEI film. The organic polymer containing phenyl can improve the flexibility of the SEI film and reduce the possibility of the SEI film rupture during repeated lithium removal and lithium insertion, thereby improving the stability of the SEI film and avoiding the consumption of excessive lithium ions in the electrolyte 140 due to the repair of the SEI film. The electrolyte 140 has good stability and the battery 100 has good cycle performance. The presence of vinyl groups makes the SEI film formed by the first additive have a higher degree of polymerization and structural stability, further inhibiting the damage of the SEI film by hydrogen fluoride in the electrolyte 140, thereby making the battery 100 have better cycle stability. The dimethyl substitution can inhibit the dissociation of hydrogen on the nitrogen atom, prevent the increase of the content of hydrogen fluoride in the electrolyte 140, and also maintain the structural stability of the first additive, and further improve the cycle performance of the battery 100.

[0048] In some embodiments, the structural formula of the second additive is: Among them, R4, R5 and R6 are all selected from siloxy groups.

[0049] It can be understood that R4, R5 and R6 can be independently selected from substituted silyl groups, and R4, R5 and R6 can also be independently selected from unsubstituted silyl groups.

[0050] In this embodiment, the structural formula of the second additive is The second additive is a phosphate additive and has a -PO- structure. When the first additive and the second additive are used together, the intermediate product formed by the reduction reaction of the first additive reacts with the second additive, so that the -PO- structure in the second additive is broken, which is convenient for further forming a C(O)-NR- structure, a -PR(=O)-NR- structure and a phosphate structure, and the second additive can also combine with lithium ions in the electrolyte 140 to form lithium phosphate after the reduction reaction, so that the SEI film formed by the first additive and the second additive has not only organic structures such as -C(O)-NR- and -PR(=O)-NR-, but also inorganic structures such as lithium phosphate. The SEI film with inorganic components has higher ionic conductivity and thermal stability. Even if the battery 100 is cycled at high temperature, the SEI film formed by the first additive and the second additive is not easily damaged, which can reduce the side reactions of active lithium ions in the electrolyte 140 at the interface of the negative electrode plate 130 and reduce the consumption of lithium ions, so that the electrolyte 140 has better thermal stability and the battery 100 has better cycle performance. Furthermore, R4, R5 and R6 are selected from silicon-oxy groups, and R4, R5 and R6 can react with hydrogen fluoride in the electrolyte to generate phosphorus-containing organic matter, and then participate in the construction of the SEI film, so that the content of lithium phosphate in the generated SEI film is higher, which is beneficial to improving the thermal stability of the SEI film, further improving the thermal stability of the electrolyte 140, and inhibiting the decomposition of the electrolyte 140.

[0051] Optionally, the general structural formula of the siloxy group is -OSiR7R8R9, where R7, R8, and R9 are selected from any group. In other words, there is no restriction on the types of R7, R8, and R9. For example, R7, R8, and R9 are each independently selected from a group such as an alkyl group, a phenyl group, and a fluorine atom.

[0052] In some embodiments, the second additive is selected from and At least one of the following, wherein TMS is a trimethylsilyl group and i-Pr is an isopropyl group.

[0053] In this embodiment, when the second additive is selected from and When at least one of the above is present, the second additive can react with the first additive to form an SEI film having an organic structure such as -C(O)-NR-, -PR(=O)-NR-, and an inorganic structure such as lithium phosphate. The SEI film having an inorganic component has higher ionic conductivity and thermal stability. Even if the battery 100 is cycled at high temperature, the SEI film formed by the first additive and the second additive is not easily damaged, which can reduce the side reactions of active lithium ions in the electrolyte 140 at the interface of the negative electrode plate 130 and reduce the consumption of lithium ions, thereby making the electrolyte 140 have better thermal stability and the battery 100 have better cycle performance. Further, and They all contain silicon elements. The silicon-containing groups can react with hydrogen fluoride in the electrolyte to generate phosphorus-containing organic matter, and then participate in the construction of the SEI film, so that the content of lithium phosphate in the generated SEI film is higher, which is beneficial to improving the thermal stability of the SEI film, further improving the thermal stability of the electrolyte 140, and inhibiting the decomposition of the electrolyte 140.

[0054] In some embodiments, the mass fraction a of the first additive is in the range of 0.05%≤a≤3%.

[0055] It can be understood that, in the electrolyte 140 , the mass fraction a of the first additive is the ratio of the mass of the first additive to the mass of the electrolyte 140 .

[0056] Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.05%, 0.08%, 0.1%, 0.3%, 0.55%, 0.6%, 0.7%, 0.85%, 0.9%, 1%, 1.2%, 1.3%, 1.45%, 1.5%, 1.6%, 1.7%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.5%, 2.6%, 2.9% and 3%, etc.

[0057] In this embodiment, when the mass fraction a of the first additive satisfies the range of 0.05%≤a≤3%, the mass fraction of the first additive is within a reasonable range. On the one hand, the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130 to reduce the contact between the solvent in the electrolyte 140 and the negative electrode plate 130, slow down the reaction between the solvent and the negative electrode plate 130, and reduce the consumption of active lithium ions while providing a stable SEI film, so that the electrolyte 140 has good stability. On the other hand, the intermediate product of the first additive in the reduction process can react with the second additive, and cooperate with the second additive to form an SEI film having both organic structures such as -C(O)-NR-, -PR(=O)-NR-, and inorganic structures such as lithium phosphate, so that the SEI film has good thermal stability. Even if the battery 100 is in a high temperature environment or the temperature rises as the charge and discharge cycle proceeds, the SEI film can still remain intact, which improves the thermal stability of the electrolyte 140, and the battery 100 has good cycle performance in a high temperature environment. When the mass fraction of the first additive is too large, the SEI film formed by the first additive is too thick, which increases the impedance of lithium ions in the electrolyte 140 passing through the SEI film, affects the dynamic performance of the battery 100, causes the battery 100 to precipitate lithium during the charge and discharge cycle, consumes too many active lithium ions, and reduces the cycle performance of the battery 100. When the mass fraction of the first additive is too small, although the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130, the SEI film formed by the first additive is difficult to completely cover the surface of the negative electrode plate 130, and the solvent in the electrolyte 140 is easy to directly contact the negative electrode plate 130 and produce side reactions to consume the lithium ions in the electrolyte 140, and this process is an irreversible loss, which reduces the cycle performance of the battery 100. Furthermore, if the mass fraction of the first additive is too large or too small, the composition of the SEI film formed by the first additive and the second additive will be too single, which is not conducive to improving the thermal stability of the SEI film. When the battery 100 is in a high temperature environment or the temperature of the battery 100 rises during the charging and discharging process, the SEI film is easily damaged and consumes more lithium ions of the electrolyte 140 for repair, thereby making the thermal stability of the electrolyte 140 low and the cycle performance of the battery 100 in a high temperature environment poor.

[0058] Preferably, the mass fraction a of the first additive is in the range of 0.3%≤a≤1%. Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.3%, 0.55%, 0.6%, 0.7%, 0.85%, 0.9% and 1%.

[0059] In some embodiments, the mass fraction b of the second additive is in the range of 0.1%≤b≤1%.

[0060] It can be understood that, in the electrolyte 140 , the mass fraction b of the second additive is the ratio of the mass of the second additive to the mass of the electrolyte 140 .

[0061] Specifically, the mass fraction b of the second additive can be, but is not limited to, 0.1%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.75%, 0.8%, 0.9% and 1%, etc.

[0062] In this embodiment, when the mass fraction b of the second additive satisfies the range of 0.1%≤b≤1%, the mass fraction of the second additive is within a reasonable range, and the second additive can be combined with the intermediate product formed by the reduction reaction of the first additive to form an SEI film having both organic structures such as -C(O)-NR-, -PR(=O)-NR-, and inorganic structures such as lithium phosphate, thereby enhancing the thermal stability of the SEI and improving the cycle performance of the battery 100 in a high temperature environment. When the mass fraction of the second additive is too large, the SEI film formed by the second additive is too thick, which increases the impedance of the lithium ions in the electrolyte 140 passing through the SEI film, affects the kinetic performance of the battery 100, causes the battery 100 to precipitate lithium during the charge and discharge cycle, consumes too many active lithium ions, and reduces the cycle performance of the battery 100. In addition, the second additive may also consume too many lithium ions to form lithium phosphate, thereby reducing the amount of active lithium ions in the electrolyte 140. When the mass fraction of the second additive is too small, the proportion of -P=O- structure in the electrolyte 140 is small. When the first additive and the second additive are used in combination, the SEI film formed by the first additive and the second additive has less lithium phosphate formed by the combination of -P=O- structure and lithium ions. In other words, the SEI film has less inorganic components, which makes the thermal stability of the SEI film poor, reducing the cycle performance of the battery 100 in a high temperature environment. Furthermore, if the mass fraction of the second additive is too large or too small, the composition of the SEI film formed by the first additive and the second additive is too single, which is not conducive to improving the thermal stability of the SEI film. When the battery 100 is in a high temperature environment or the temperature of the battery 100 rises during the charging and discharging process, the SEI film is easily damaged and consumes more lithium ions in the electrolyte 140 for repair, which makes the thermal stability of the electrolyte 140 low and the cycle performance of the battery 100 in a high temperature environment is poor.

[0063] Preferably, the mass fraction b of the second additive is in the range of 0.2%≤b≤0.5%. Specifically, the mass fraction b of the second additive may be, but is not limited to, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, etc.

[0064] In some embodiments, in the electrolyte 140 , the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte 140 satisfies the relationship: 0.1≤a / b≤5.

[0065] Specifically, the value of a / b can be, but is not limited to, 0.1, 0.2, 0.35, 0.5, 0.6, 0.8, 0.9, 1, 1.1, 1.3, 1.4, 1.5, 1.7, 1.8, 1.9, 2, 2.1, 2.3, 2.5, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.7 and 5, etc.

[0066] In this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship 0.1≤a / b≤5, the value of the mass fraction a of the first additive and the value of the mass fraction b of the second additive are both within a reasonable range, and the first additive and the second additive have a good synergistic effect, so that the SEI film formed by the first additive and the second additive in a high temperature environment has good stability, thereby making the electrolyte 140 have good stability. Specifically, the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130 to reduce the contact between the solvent in the electrolyte 140 and the negative electrode plate 130, slow down the reaction between the solvent and the negative electrode plate 130, and reduce the consumption of active lithium ions while providing a stable SEI film, thereby making the electrolyte 140 have good stability. In addition, the amount of the intermediate product of the first additive during the reduction process is within a reasonable range, and it can react synergistically with the second additive to form an SEI film having both organic structures such as -C(O)-NR-, -PR(=O)-NR-, and inorganic structures such as lithium phosphate, thereby making the SEI film have good thermal stability. Even when the battery 100 is in a high temperature environment or the temperature rises as the charge and discharge cycle proceeds, the SEI film can still remain intact, thereby improving the thermal stability of the electrolyte 140, and the battery 100 has good cycle performance in a high temperature environment. When the value of a / b is too large, the mass fraction of the first additive is too large, or the mass fraction of the second additive is too small, which may, on the one hand, cause the SEI film formed by the first additive and the second additive to be too thick, thereby increasing the internal resistance of the battery 100, thereby reducing the cycle performance of the battery 100; on the other hand, it may cause the content of inorganic components such as lithium phosphate in the formed SEI film to be too low, thereby causing the thermal stability of the SEI film to decrease, the capacity retention rate of the battery 100 in a high temperature environment to decrease, and the high temperature cycle performance of the battery 100 is also poor. When the value of a / b is too small, the mass fraction of the first additive is too small, or the mass fraction of the second additive is too large. Although the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130, the SEI film formed by the first additive is difficult to completely cover the surface of the negative electrode plate 130. The solvent in the electrolyte 140 is easy to directly contact the negative electrode plate 130 and produce a side reaction to consume the lithium ions in the electrolyte 140. This process is an irreversible loss, which reduces the cycle performance of the battery 100. In addition, the first additive generates fewer intermediate products during the reduction process, which is difficult to effectively combine with the second additive, making it difficult for the second additive to form lithium phosphate, and also resulting in too low a content of inorganic components such as lithium phosphate in the formed SEI film, resulting in a decrease in the thermal stability of the SEI film, a decrease in the capacity retention rate of the battery 100 in a high temperature environment, and poor high temperature cycle performance of the battery 100.Therefore, if the value of a / b is too large or too small, the composition of the SEI film formed by the first additive and the second additive will be too single, so that the thermal stability of the electrolyte 140 is poor.

[0067] Preferably, the electrolyte 140 satisfies the relationship: 1≤a / b≤2. Specifically, the value of a / b may be, but is not limited to, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc.

[0068] Optionally, in some embodiments, the electrolyte 140 further satisfies the relationship: 0.6%≤a+b≤1.5%. Specifically, the value of a+b can be, but is not limited to, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0069] In this embodiment, when the electrolyte 140 satisfies the relationship 0.6%≤a+b≤1.5%, the mass fraction of the first additive and the mass fraction of the second additive in the electrolyte 140 are both within a reasonable range, and the first additive and the second additive have a good synergistic effect, so that the SEI film formed by the first additive and the second additive in a high temperature environment has good stability, thereby making the electrolyte 140 have good stability. When the electrolyte 140 is applied to the battery 100, the battery 100 has good cycle performance.

[0070] The technical solution of this application is further introduced in the following with multiple embodiments:

[0071] Example 1 to Example 31, Comparative Example 1 to Comparative Example 6:

[0072] 1. Preparation of electrolyte 140:

[0073] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a mass ratio of 1:1:1, and then the dried electrolyte lithium salt lithium hexafluorophosphate is dissolved in the solvent, stirred until completely dissolved and uniformly dissolved, and the first additive and the second additive are added. After mixing evenly, the electrolyte 140 of Examples 1 to 31 and Comparative Examples 1 to 6 is obtained. The obtained electrolyte 140 is composed as follows: the solvent composition is ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 1:1:1, and the lithium salt concentration is 1 mol / L;

[0074] Among them, the type of the first additive, the mass fraction a of the first additive, the type of the second additive, the mass fraction b of the second additive, and the value of a / b in the electrolyte 140 of Examples 1 to 31 and Comparative Examples 1 to 6 are shown in Table 1.

[0075] 2. Preparation of positive electrode sheet 110:

[0076] The positive electrode active material lithium iron phosphate, the positive electrode conductive agent conductive carbon black (SP), and the positive electrode binder polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methyl-2-pyrrolidone (NMP) according to a ratio and mixed evenly to obtain a positive electrode slurry with a solid content of 60wt%. The positive electrode slurry is coated on the positive electrode collector (aluminum foil), and the coating weight of the positive electrode slurry is 300mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet 110 is obtained.

[0077] 3. Preparation of negative electrode sheet 130:

[0078] The negative electrode active material hard carbon, the negative electrode conductive agent conductive carbon black (SP), the negative electrode thickener carboxymethyl cellulose (CMC), the negative electrode binder styrene butadiene rubber (SBR) and asphalt are dispersed in deionized water according to a ratio and mixed evenly to obtain a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is coated on the negative electrode collector (copper foil). The coating weight of the negative electrode slurry is 144mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet 130 is obtained.

[0079] 4. Preparation of the diaphragm 120:

[0080] The diaphragm 120 is a 16 um polyethylene film.

[0081] 5. Preparation of Battery 100:

[0082] The prepared positive electrode sheet 110, separator 120, and negative electrode sheet 130 are stacked in order so that the separator 120 is located between the positive electrode sheet 110 and the negative electrode sheet 130, and the positive electrode sheet 110, separator 120, and negative electrode sheet 130 are wound to obtain an electrode assembly, and the electrode assembly is assembled into an outer package after welding the electrode ears, and after injecting the prepared electrolyte 140, the battery cells are packaged, allowed to stand, formed, shaped, and capacity tested, and finally implementation batteries 1 to implementation batteries 31 and comparison batteries 1 to comparison batteries 6 are prepared.

[0083] Among them, the electrolyte 140 of Example 1 is applied to the implementation battery 1, the electrolyte 140 of Example 2 is applied to the implementation battery 2, the electrolyte 140 of Comparative Example 1 is applied to the comparison battery 1, the electrolyte 140 of Comparative Example 2 is applied to the comparison battery 2, and so on.

[0084] The following Table 1 is a table of component parameters of the electrolyte 140 of Examples 1 to 31 and Comparative Examples 1 to 6.

[0085] Table 1: Composition parameters of the electrolyte 140 of Examples 1 to 31 and Comparative Examples 1 to 6.

[0086]

[0087]

[0088] It can be understood that the electrolyte 140 of comparative example 1 includes neither the first additive nor the second additive, the electrolyte 140 of comparative example 2 includes only the first additive but not the second additive, and the electrolyte 140 of comparative example 3 includes only the second additive but not the first additive.

[0089] Among them, in Table 1, the structural formula of Formula 1-1 of the first additive is The structural formula of the first additive of formula 1-2 is The structural formula of Formula 1-3 of the first additive is The structural formula of Formula 1-4 of the first additive is The structural formula of Formula 1-5 of the first additive is The structural formula of Formula 1-6 of the first additive is

[0090] In Table 1, the structural formula of the second additive 2-1 is The structural formula of the second additive 2-2 is The structural formula of the second additive of formula 2-3 is The structural formula of the second additive of formula 2-4 is

[0091] Performance test of battery 100:

[0092] Testing of the cycle performance of Implementation Battery 1 to Implementation Battery 31 and Comparative Battery 1 to Comparative Battery 6 at high temperature:

[0093] The above-mentioned implementation batteries 1 to implementation batteries 31 and comparison batteries 1 to comparison batteries 6 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 45°C, the charge and discharge rate was 1P (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge power = battery 100 voltage platform (3.2V) × rated capacity of battery 100), the charge and discharge voltage window was 2.5V to 3.65V (that is, the charge cut-off voltage of battery 100 is 3.65V, and the discharge cut-off voltage of battery 100 is 2.5V; it is generally believed that when the charge cut-off voltage is ≥4V, the charge cut-off voltage of battery 100 is higher), and the capacity retention rate after 1000 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.

[0094] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 100 is first charged from 2.5V to 3.65V, and then discharged from 3.65V to 2.5V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.

[0095] Table 2 shows the capacity retention rates of Example Batteries 1 to 31 and Comparative Batteries 1 to 6 after 1000 cycles at 45° C.

[0096] Table 2 below shows the performance parameters of implementation batteries 1 to implementation batteries 31 and comparison batteries 1 to comparison batteries 6.

[0097] Table 2: Performance parameters of implementation batteries 1 to implementation batteries 31 and comparative batteries 1 to comparative batteries 6.

[0098]

[0099]

[0100] It can be understood that the capacity retention rate after 1000 cycles at 45°C can represent the cycle performance of the battery 100 in a high temperature environment. The greater the capacity retention rate after 1000 cycles at 45°C, the better the cycle performance of the battery 100 in a high temperature environment.

[0101] Please refer to Table 1 and Table 2. It can be seen from the data of Comparative Examples 1 to Comparative Examples 3 and Examples 1 to Examples 31 that the capacity retention rates of Comparative Batteries 1 to Comparative Batteries 3 after 1000 cycles at 1P at 45°C are lower than the capacity retention rates of Implementation Batteries 1 to Implementation Batteries 31 after 1000 cycles at 1P at 45°C. This is because: the electrolyte 140 of Comparative Example 1 includes neither the first additive nor the second additive. During the charge and discharge cycle of the battery 100, as lithium ions are embedded in and extracted from the surface of the negative electrode plate 130, the SEI film is constantly expanding and contracting, resulting in poor cycle stability of the SEI film at high temperatures. Therefore, the SEI film is constantly destroyed and repaired, and the process of generating the SEI film is the process in which the components of the electrolyte 140 gain and lose electrons on the surface of the active material. This process is accompanied by the loss of active lithium ions, and it is an irreversible loss. The reduction in the content of active lithium ions leads to poor charge and discharge cycle capacity of the comparative battery 1. The electrolyte 140 of Comparative Example 2 includes only the first additive but not the second additive, and the electrolyte 140 of Comparative Example 3 includes only the second additive but not the first additive. The cycle performance of Comparative Battery 2 and Comparative Battery 3 is slightly improved compared with Comparative Battery 1. However, when the electrolyte 140 includes only at least one of the first additive and the second additive, the first additive and the second additive cannot work synergistically. In other words, the stability of the SEI film formed by the electrolyte 140 of Comparative Example 2 and Comparative Example 3 is still poor, so that the stability of the electrolyte 140 is poor, and the cycle performance of Comparative Battery 2 and Comparative Battery 3 is poor.

[0102] Please refer to the data of Examples 1 to 20. In the first aspect, from the data of Examples 1 to 5 and Comparative Example 4, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 1 to 5 is The mass fraction a of the first additive satisfies the range of 0.05%≤a≤3%, and a / b satisfies the range of 0.1≤a / b≤5, while the mass fraction of the first additive in comparative example 4 is less than 0.05%, and the value of a / b is less than 0.1, which makes the capacity retention rate of implementation battery 1 to implementation battery 5 at 45°C and 1P for 1000 cycles higher than the capacity retention rate of comparison battery 4 at 45°C and 1P for 1000 cycles, and as the mass fraction of the first additive gradually increases, the cycle performance of the corresponding battery 100 first increases and then decreases, because: when the value of a is within a reasonable range, and a / b is within a reasonable range, the first additive and the second additive have good synergistic The first additive can preferentially form an SEI film on the surface of the negative electrode plate 130 to reduce the contact between the solvent in the electrolyte 140 and the negative electrode plate 130, slow down the reaction between the solvent and the negative electrode plate 130, and reduce the consumption of active lithium ions while providing a stable SEI film. In addition, the amount of the intermediate product of the first additive during the reduction process is within a reasonable range, and can synergistically react with the second additive to form an SEI film having both organic structures such as -C(O)-NR-, -PR(=O)-NR-, and inorganic structures such as lithium phosphate, so that the SEI film has better thermal stability, so that the corresponding battery 100 has better cycle performance. Furthermore, when the value of the mass fraction a of the first additive is too small or too small, although the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130, the SEI film formed by the first additive is difficult to completely cover the surface of the negative electrode plate 130, and the solvent in the electrolyte 140 is easy to directly contact the negative electrode plate 130 and produce a side reaction to consume the lithium ions in the electrolyte 140, and this process is an irreversible loss, which reduces the cycle performance of the battery 100. When the value of the mass fraction a of the first additive is too large, the SEI film formed by the first additive is too thick, which increases the impedance of the lithium ions in the electrolyte 140 passing through the SEI film, affects the kinetic performance of the battery 100, causes the battery 100 to precipitate lithium during the charge and discharge cycle, consumes too many active lithium ions, and reduces the cycle performance of the battery 100. Therefore, as the mass fraction a of the first additive increases, the corresponding cycle performance of the battery 100 first increases and then decreases.

[0103] Similarly, from the data of Examples 6 to 8, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 6 to 8 is And as the mass fraction of the first additive gradually increases, the corresponding cycle performance of the battery 100 first increases and then decreases. From the data of Examples 9 to 11, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 9 to 11 is And as the mass fraction of the first additive gradually increases, the corresponding cycle performance of the battery 100 first increases and then decreases. From the data of Examples 12 to 14, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 12 to 14 is And as the mass fraction of the first additive gradually increases, the corresponding cycle performance of the battery 100 first increases and then decreases. From the data of Examples 15 to 17, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 15 to 17 is And as the mass fraction of the first additive gradually increases, the corresponding cycle performance of the battery 100 first increases and then decreases. From the data of Examples 18 to 20, it can be seen that the structural formula of the first additive in the electrolyte 140 of Examples 18 to 20 is And as the mass fraction of the first additive gradually increases, the corresponding cycle performance of the battery 100 first increases and then decreases.

[0104] Furthermore, it can be seen from the data of Example 3, Example 7, Example 10, Example 13, Example 16 and Example 19 that, under the same other conditions, the type of the first additive of the electrolyte 140 can affect the cycle performance of the battery 100. Among them, the first additives of Example 3 and Example 7 include fluorine, which increases the content of LiF in the SEI film generated by them, thereby improving the thermal stability and acid resistance of the SEI film. The first additive of Example 13 includes phenyl, and the polymer containing phenyl is conducive to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and delithiation, thereby improving the high temperature performance of the implementation battery 13. The first additive of Example 16 includes vinyl, so that the SEI film formed by the first additive has a higher degree of polymerization and structural stability, further inhibiting the damage of the SEI film by hydrogen fluoride in the electrolyte 140, so that the implementation battery 16 has better cycle stability. The first additive of Example 19 includes a dimethyl group, which can inhibit the dissociation of hydrogen on the nitrogen atom and prevent the increase of the content of hydrogen fluoride in the electrolyte 140. At the same time, it can also maintain the structural stability of the first additive and further implement the cycle performance of the battery 19.

[0105] Please refer to the data of Example 21 to Example 24. The mass fraction b of the second additive in Example 21 to Example 24 satisfies the range of 0.1%≤b≤1%, and the range of a / b also satisfies the range of 0.1≤a / b≤5. As the mass fraction of the second additive increases, the corresponding cycle performance of the battery 100 first increases and then decreases. This is because: when the value of b is within a reasonable range, and a / b is within a reasonable range, the second additive can be combined with the intermediate product formed by the reduction reaction of the first additive to form an SEI film having both organic structures such as -C(O)-NR-, -PR(=O)-NR-, and inorganic structures such as lithium phosphate, thereby enhancing the thermal stability of the SEI and improving the cycle performance of the battery 100 in a high temperature environment. Therefore, the cycle capacity retention rate of the implementation battery 22 and the implementation battery 23 is relatively high. When the value of b is too small, the proportion of -P=O- structure in the electrolyte 140 is small. When the first additive and the second additive are used in combination, the SEI film formed by the first additive and the second additive has less lithium phosphate formed by the combination of -P=O- structure and lithium ions. In other words, there are fewer inorganic components in the SEI film, which makes the thermal stability of the SEI film poor, reducing the cycle performance of the battery 100 in a high temperature environment. Therefore, the cycle capacity retention rate of the implemented battery 21 is low. When the value of b is too large, the SEI film formed by the second additive is too thick, which increases the impedance of lithium ions in the electrolyte 140 passing through the SEI film, affects the kinetic performance of the battery 100, causes the battery 100 to precipitate lithium during the charge and discharge cycle, consumes too many active lithium ions, and reduces the cycle performance of the battery 100. In addition, the second additive may also consume too many lithium ions to form lithium phosphate, thereby reducing the amount of active lithium ions in the electrolyte 140, so the cycle capacity retention rate of the implemented battery 24 is low.

[0106] Please refer to the data of Examples 3, 25 to 27. Under the same other conditions, the type of the second additive in the electrolyte 140 may affect the cycle performance of the battery 100. The structural formula of the second additive in Example 3 is The structural formula of the second additive of Example 25 is The structural formula of the second additive of Example 26 is The structural formula of the second additive of Example 27 is Among them, the capacity retention rate of the embodiment battery 27 after 1000 cycles at 1P at 45°C is the highest. This is because: the second additive of the embodiment 27 contains more fluorine atoms, so that there are more LiF in the SEI film formed by the first additive and the second additive, so that the SEI film has higher thermal stability, so that the embodiment battery 27 has better cycle performance under high temperature environment. In addition, the second additives of the embodiments 3, 25 and 27 all include siloxy groups, which can react with hydrogen fluoride in the electrolyte to generate phosphorus-containing organic matter, and then participate in the construction of the SEI film, so that the content of lithium phosphate in the generated SEI film is higher, which is conducive to improving the thermal stability of the SEI film, further improving the thermal stability of the electrolyte 140, and inhibiting the decomposition of the electrolyte 140, so that the corresponding battery 100 has higher stability.

[0107] Please refer to the data of Examples 28 to 31, Comparative Examples 5 and 6. When the sum of the mass fraction of the first additive and the mass fraction of the second additive is constant, the value of a / b can be regulated by adjusting the value of the mass fraction a of the first additive and the value of the mass fraction b of the second additive. The value of a / b in the electrolyte 140 of Examples 28 to 31 satisfies the range of 0.1≤a / b≤5, while the value of a / b in the electrolyte 140 of Comparative Example 5 is too small, and the value of a / b in the electrolyte 140 of Comparative Example 7 is too large, so that the electrolyte 140 of Examples 28 to 31 is not as good as that of Comparative Example 7. The capacity retention rate of cell 31 after 1000 cycles at 1P at 45°C is higher than that of comparison cell 5 and comparison cell 6 after 1000 cycles at 1P at 45°C, and as the value of a / b gradually increases, the cycle performance of the corresponding battery 100 first increases and then decreases. This is because: when the value of a / b is within a reasonable range, the first additive and the second additive have a good synergistic effect, so that the SEI film formed by the first additive and the second additive in a high temperature environment has good stability, thereby making the electrolyte 140 have good stability. When the value of a / b is too large or too large, the SEI film formed by the first additive and the second additive may be too thick, thereby increasing the internal resistance of the battery 100, thereby reducing the cycle performance of the battery 100; it may also cause the content of inorganic components such as lithium phosphate in the formed SEI film to be too low, thereby causing the thermal stability of the SEI film to decrease, the capacity retention rate of the battery 100 in a high temperature environment to decrease, and the high temperature cycle performance of the battery 100 is also poor. When the value of a / b is too small or too small, although the first additive can preferentially form an SEI film on the surface of the negative electrode plate 130, the SEI film formed by the first additive is difficult to completely cover the surface of the negative electrode plate 130, and the solvent in the electrolyte 140 is easy to directly contact the negative electrode plate 130 and produce a side reaction to consume the lithium ions in the electrolyte 140, and this process is an irreversible loss, which reduces the cycle performance of the battery 100. In addition, the first additive generates fewer intermediate products during the reduction process, which is difficult to effectively combine with the second additive, making it difficult for the second additive to form lithium phosphate, and also resulting in too low a content of inorganic components such as lithium phosphate in the formed SEI film, resulting in a decrease in the thermal stability of the SEI film, a decrease in the capacity retention rate of the battery 100 in a high temperature environment, and poor high temperature cycle performance of the battery 100.

[0108] See also Figure 2 and Figure 3 The present application also provides an electrical device 200 , which includes: a device body 210 and a battery 100 provided in the present application, and the battery 100 supplies power to the device body 210 .

[0109] It can be understood that the battery 100 is electrically connected to the device body 210 .

[0110] In this embodiment, the electrolyte 140 of the battery 100 includes a first additive and a second additive, wherein the first additive is a hydantoin additive, and the second additive is a phosphate additive, and the first additive and the second additive have a synergistic effect, so that the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 130 has good chemical stability and thermal stability, which can slow down the side reactions between other components in the electrolyte 140 and the negative electrode plate 130 and consume lithium ions in the electrolyte 140, and can also reduce the lithium ions lost in repair due to the rupture of the SEI film, and can reduce the life attenuation amplitude of the battery 100, so that the battery 100 has good cycle performance in a high temperature environment, and the battery 100 has a long service life. When the battery 100 is applied to the electrical device 200, the battery 100 can provide stable power for the device body 210, which is conducive to improving the user experience.

[0111] Optionally, the power-consuming device 200 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 2 The electrical equipment 200 of the embodiment is an energy storage battery cabinet.

[0112] It can be understood that the electric device 200 described in this embodiment is only one form of the electric device 200 used by the battery 100, and should not be understood as a limitation on the electric device 200 provided in this application, nor should it be understood as a limitation on the electric device 200 provided in each embodiment of this application.

[0113] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0114] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes a first additive and a second additive, wherein the first additive is a hydantoin additive, and the second additive is a phosphate additive.

2. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 0.1≤a / b≤5.

3. The electrolyte according to claim 1, characterized in that The structural formula of the first additive is: Among them, R1 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, R2 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, and nitro, and R3 is selected from at least one of hydrogen, halogen, methyl, trifluoromethyl, phenyl, cyano, nitro, and vinyl.

4. The electrolyte according to claim 3, characterized in that The first additive is selected from and At least one of .

5. The electrolyte according to claim 2, characterized in that The mass fraction a of the first additive is in the range of 0.05%≤a≤3%.

6. The electrolyte according to claim 1, characterized in that The structural formula of the second additive is: Wherein, R4, R5 and R6 are all selected from siloxy groups.

7. The electrolyte according to claim 6, characterized in that The second additive is selected from and At least one of the following, wherein TMS is a trimethylsilyl group and i-Pr is an isopropyl group.

8. The electrolyte according to claim 2, characterized in that The mass fraction b of the second additive is in the range of 0.1%≤b≤1%.

9. A battery, characterized in that: The battery comprises: Positive electrode; Diaphragm; A negative electrode; and The electrolyte according to any one of claims 1 to 8, wherein the electrolyte is used to wet the positive electrode sheet, the separator and the negative electrode sheet.

10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.

Citation Information

Patent Citations

  • Electrolyte additive, electrolyte, lithium battery and electric equipment

    CN116093431A

  • Resist underlayer film-forming composition containing reaction product of hydantoin compound

    CN116157447A

  • Electrolyte and battery

    CN116666756A

  • Electrolyte of aqueous bimetal cation battery as well as preparation method and application of electrolyte

    CN118589065A

  • Lithium metal secondary battery containing an elastic anode-protecting layer

    WO2020086117A1